AS INTERVENÇÕES DO PIM COMO OBJETO DE ANÁLISE: PIM'S INTERVENTIONS AS OBJECT OF ANALYSIS (Revista Contexto & Educação, 2021)
Early childhood, considering birth to 7 years of age, needs essential care for the healthy development of the child, thus bringing socioeconomic impacts to society. As for public policies, programs that encourage activities related to the integral development of this stage of life are essential, contributing to optimize the cognitive and socioemotional development of children. In this sense, the First Childhood Better Program (PIM), created by the State Government of Rio Grande do Sul and coordinated by the State Health Secretariat and with support from the Secretariats of Culture, Education, Labor and Social Development, is a government policy that serves vulnerable families with pregnant women and children aged 0-3 years, referred, in particular, by UBSF. Children discharged from the Intensive Care Unit (ICU) are also part of this target audience and require special attention. Considering that scientific production, in addition to promoting the dissemination of public policy, simultaneously contributes to the analysis, reflection and discussion of programs, which contributes to the qualification of the actions involved, the article presented here aims to generate an overview of scientific production that has as its theme the approach of this Public Policy.
Keywords: childhood, mediation, child development, public policy